Studi Perbandingan Akuntansi Kombinasi Bisnis di Indonesia dan Malaysia: Tantangan dan Solusinya - Nabila Yolanda; Dina Izzati; Vista Alisha Zahrani; Suci Ramadhani; Bana Ahmad Gautama (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to compare business combination accounting practices in Indonesia and Malaysia, as well as identify challenges and solutions for implementation. Using a qualitative descriptive approach based on a literature study for 2021-2025, the accounting standards used, namely PSAK 22, PSAK 38, and PSAK 65 in Indonesia and MFRS 3 and MFRS 10 in Malaysia, were analysed. Although both refer to IFRS, there are significant differences, especially in transactions between entities under common control. Indonesia has flexibility through PSAK 38, while Malaysia has no explicit guidelines. The study results show that business combinations do not always improve financial performance. Challenges faced include regulatory dualism, limited human resources, lack of transparency, and post-merger integration barriers. Proposed solutions include harmonisation of standards with IFRS, HR training, increased transparency, and regulatory reform. In Indonesia, financial literacy, particularly in the Islamic sector, is still low and affects the effectiveness of business combinations. Meanwhile, Malaysia faces constraints in its merger supervision system as it does not yet have a mandatory notification system. Hence, there is a need for regulatory evaluation and cross-agency collaboration to establish an adaptive and sustainable system.